Evolutionary game and simulation analysis on management synergy in China’s coal emergency coordination - Shi, Peizhe; Hao, Yu; Sun, Chaolun; Zhang, LiJun (Frontiers in Environmental Science, 2023)
The post-processing of coal mine accidents requires the emergency coordination of multiple departments and related personnel. However, due to the differences in interest motives, preferences and cognitive structures among these related subjects, it is difficult to avoid cooperation and conflicts in coordinated actions. Therefore, in order for emergency managers to make correct decisions in a complex conflict environment, it is necessary to sort out and analyze the game relationship between conflict and cooperation among relevant subjects. Based on the perspective of evolutionary game theory, this study establishes a game model of coal mine accident response behavior between coal mining enterprises and local governments, and quantitatively adopts the method of numerical simulation analysis to conduct in-depth analysis of the influencing factors of their decision-making behavior, and then draws guidance, meaningful policy guidance. According to the research results, the establishment of an information sharing mechanism is an important condition for local governments to efficiently and quickly start the incident response process for coal mine accidents. The cost of emergency response is the decisive factor affecting the incident response work of coal mining company. In addition, the establishment of emergency cost compensation mechanism and incentive mechanism should also be the focus of local governments in formulating emergency coordination policies in the future.